2007
DOI: 10.1097/yic.0b013e3281c55f4f
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, placebo-controlled, randomized study evaluating the effect of paliperidone extended-release tablets on sleep architecture in patients with schizophrenia

Abstract: The effects of paliperidone extended-release on sleep architecture in patients with schizophrenia-related insomnia were evaluated in this multicenter, double-blind, randomized, placebo-controlled study. Patients received paliperidone extended-release 9 mg/day or matching placebo during the 14-day double-blind phase. Sleep architecture and sleep continuity were evaluated using polysomnograms. Subjective sleep measures were evaluated daily using the Leeds Sleep Evaluation Questionnaire. Efficacy and safety were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 26 publications
4
35
0
1
Order By: Relevance
“…groups are consistent with data from studies of the oral formulation, paliperidone ER 5Y7 ; including a study that specifically investigated the effects of paliperidone ER on the sleep architecture and sleep continuity in patients with schizophrenia experiencing insomnia. 19 The incidence of discontinuations across treatment groups in this study (45%Y48% in the paliperidone palmitate groups, 57% in the placebo group) is consistent with rates reported in other drug studies in schizophrenia 20,21 and with rates observed in previous paliperidone palmitate studies. 9,10 One limitation of this study is that an active comparator was not included; hence, the relative efficacy of paliperidone palmitate compared with other active treatments is not known.…”
Section: Discussionsupporting
confidence: 88%
“…groups are consistent with data from studies of the oral formulation, paliperidone ER 5Y7 ; including a study that specifically investigated the effects of paliperidone ER on the sleep architecture and sleep continuity in patients with schizophrenia experiencing insomnia. 19 The incidence of discontinuations across treatment groups in this study (45%Y48% in the paliperidone palmitate groups, 57% in the placebo group) is consistent with rates reported in other drug studies in schizophrenia 20,21 and with rates observed in previous paliperidone palmitate studies. 9,10 One limitation of this study is that an active comparator was not included; hence, the relative efficacy of paliperidone palmitate compared with other active treatments is not known.…”
Section: Discussionsupporting
confidence: 88%
“…These results are generally consistent with those from other recent studies of paliperidone palmitate for both the acute and maintenance treatment of patients with schizophrenia (Gopal et al, 2010;Hough et al, 2008Hough et al, , 2009Kramer et al, 2010), as well as for the oral formulation, paliperidone (Davidson et al, 2007;Kane et al, 2007;Kramer et al, 2007;Luthringer et al, 2007;Marder et al, 2007). Although in this study, paliperidone palmitate was administered gluteally, it may be administered in the deltoid muscle as well (Hough et al, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…In this context, Luthringer et al (2007) conducted a randomized, double-blind, placebo-controlled, 3-week study in patients (n = 42) with schizophrenia-related insomnia to assess the effect of paliperidone ER (dosed Q AM) on sleep architecture. They also assessed the effect of this antipsychotic on patient-rated changes in sleep quality and daytime drowsiness based on the pooled data from the three pivotal trials.…”
Section: Resultsmentioning
confidence: 99%